2008
DOI: 10.1029/2007wr006523
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the dissolved organic carbon output from a boreal mire using the convection‐dispersion equation: Importance of representing sorption

Abstract: [1] In this paper we present a model of the dissolved organic carbon (DOC) concentrations and fluxes in mire water based on the convection-dispersion equation. The dynamics of sorbed, potentially soluble organic carbon (SPSOC) in the peat matrix are simulated in parallel with DOC. First, the model is applied solely to stagnant water conditions in order to interpret the results of laboratory peat incubations, with the focus on sorption processes. Some important model parameters are derived using literature data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
96
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(100 citation statements)
references
References 49 publications
(65 reference statements)
4
96
0
Order By: Relevance
“…The C4 dilution can be attributed to less water infiltrating and subsequent reduced contact time with peat Yurova et al, 2008). Similar autumn dilution pattern in C7 (Köhler et al, 2008) can be attributed to the influence of the upstream mire during the autumn season.…”
Section: Climate Control On Docmentioning
confidence: 57%
See 2 more Smart Citations
“…The C4 dilution can be attributed to less water infiltrating and subsequent reduced contact time with peat Yurova et al, 2008). Similar autumn dilution pattern in C7 (Köhler et al, 2008) can be attributed to the influence of the upstream mire during the autumn season.…”
Section: Climate Control On Docmentioning
confidence: 57%
“…Vegetation in the mires mainly consists of Sphagnum sp. (Yurova et al, 2008). The region has a long-term mean air temperature of with the highest temperatures occurring in July.…”
Section: Site Descriptions and Stream Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…The strength of the model proposed by Lumsdon et al (2005) is its focus on organic carbon solubility in the soil. The Mire DOC model proposed by Yurova et al (2008), works well for peaty wetlands, but might not be able to give a credible representation of the contrasting mechanisms controlling DOC in forest streams. The wide variation in process understanding, conceptualization and representation in these DOC models could lead to large uncertainties that could potentially be of the same order of magnitude as the uncertainty associated with future climate projections or even larger.…”
Section: Introductionmentioning
confidence: 99%
“…SMR of time-lagged climate and deposition parameters has shown that changes in acidic deposition can explain substantial proportions of long-term trends in surface water [DOC] in a series of Norwegian catchments Futter and de Wit 2008). End-member mixing analysis has been applied to simulate streamwater [DOC] as a function of inputs from catchment soils and wetlands (Easthouse et al 1992), and a physically based model of DOC production and transport in boreal mires has been presented (Yurova et al 2007). Detailed chemical modeling can also help to elucidate effects of soil water variables on surface water [DOC] (Löfgren et al 2010b).…”
Section: Introductionmentioning
confidence: 99%